Natural capital preservation and sustainable management as a prerequisite for year-round tourism - Runko Luttenberger, Lidija (Array, 2019)
Increasing number of tourists wants to experience nature and at the same time have a positive impact on nature during their tourist stay. This paper presents the relationship between the preservation of natural capital of the locality and tourist season duration, as well as destination sustainable management and longevity. Tourism greatly depends on natural world, meaning the beauty of landscapes and seascapes and man's connection with nature itself. It simultaneously depends on local natural environment and exerts an impact thereon. Conservation and sustainable management of natural capital maybe achieved in various ways. Countries are attempting to preserve natural capital and to monitor its change through regular reporting, using selected indicators. Croatia should strive to preserve its unique natural resources and devise the tools to measure own performance with due consideration of its specific feature, all with the aim of ensuring sustainable all-year tourism. Finally, the paper considers comprehensively all pressures on natural environment exerted by tourism as well as benefits for the locality of preserving domestic natural capital in a long term, while ensuring the monitoring of changes in state thereof. A 'high value, low impact' approach would bring in the growing share of affluent nature-loving tourists throughout the year, thus reducing present tourism seasonality and highly negative impact on nature, local communities and microclimate change.